India: Agricultural Marketing Information Network - Agmarknet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agmarknet makes available reliable market information on the quantities and prices of different commodities and helps farmers make decisions and strengthen their bargaining power. In the past information was disseminated through radio, newspapers, blackbo